The median effective doses of propofol combined with two different doses of nalbuphine for adult patients during painless gastroscopy - Tang, Lili; Ye, Chenxuan; Wang, Nan; Chen, Chen; Chen, Sirui; Gao, Shan; Liu, Xuesheng (Frontiers in Pharmacology, 2022)
Objective Propofol is the most widely administered intravenous anesthetics to introduce deep sedation for gastroscopy procedures. Nalbuphine is added to reduce the dose of propofol required and propofol-related adverse events, providing analgesia to visceral pain and sedation. Our study aimed to determine the median effective dose (ED50) of propofol combined with different doses of nalbuphine in painless gastroscopy. Methods Sixty-one patients aged 18 to 60 years who were recruited for elective painless gastroscopy were allocated randomly to the N1 group (0.1 mg/kg nalbuphine) and N2 group (0.15 mg/kg nalbuphine). Three minutes after administration of nalbuphine, patients received propofol at a preselected dose according to the Dixon “up-and-down” method starting at 2.0 mg/kg with a step size of 0.2 mg/kg. The primary outcome was the ED50 of propofol combined with nalbuphine. Secondary outcomes included: hemodynamic parameters, adverse events, visual analogue scale(VAS) score at the point of anaesthesia recovery, and recovery time. Results The ED50 of propofol in the N2 group was significantly lower than that observed in the N1 group (P = .005). Using probit analysis, the ED50 and ED95 of propofol were 1.632 mg/kg and 2.759 mg/kg in the N1 group, 1.111 mg/kg and 2.243 mg/kg in the N2 group, respectively. The incidence of hypotension in the N2 group was lower than that in the N1 group (P = .011), and the recovery time was shorter than that of the N1 group (P = .014). Conclusion The ED50 and ED95 of propofol in the N2 group were both significantly lower. It also reduced the incidence of hypotension and shortened the recovery time. Therefore, nalbuphine (0.15mg/kg) is recommended for safety and enhanced recovery of painless gastroscopy.